(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The posterior palatal seal is essential for the retention and stability of maxillary complete dentures. The fovea palatini and the vibrating line are critical anatomical landmarks used to determine the denture’s posterior extent. However, variability in their spatial relationship across populations may affect the accuracy of denture border placement. Limited data exist from South Asian populations, particularly in clinical settings, regarding this anatomical relationship. Objective: To evaluate the positional relationship between the fovea palatini and the vibrating line in a sample of patients at a tertiary care dental hospital and to assess its association with age and gender. Methods: A descriptive cross-sectional study was conducted over six months at the Department of Prosthodontics, Bacha Khan College of Dentistry, Mardan. A total of 151 patients aged 20–80 years with visible fovea palatini and normal palatal mucosa were included using consecutive non-probability sampling. The vibrating line was identified using the phonation method and recorded relative to the fovea palatini as anterior, coinciding, or posterior. Associations with age and gender were analyzed using Chi-square tests. Data were processed using SPSS version 25, and a p-value of <0.05 was considered statistically significant. Results: The vibrating line was located anterior to the fovea palatini in 104 participants (68.8%), at the fovea in 29 (19.2%), and posterior in 18 (11.9%). No significant associations were found between vibrating line position and gender (p = 0.96) or age group (p = 0.81). Conclusion: The vibrating line most frequently lies anterior to the fovea palatini, indicating that sole reliance on the foveal landmark may result in underextension of maxillary dentures. Functional assessment using phonation should be employed alongside anatomical guidance to ensure optimal posterior palatal seal and denture retention. Future studies should incorporate broader populations and palatal morphology to refine prosthodontic protocols.